An artificial neural network-based DSS to prioritise information technology and its complementary investments in industrial firms. (1st January 2012) - Keramati, Abbas; Mojir, Navid; Afshari-Mofrad, Masoud; Jahanandish, Iman; Derakhshani, Ali
The impact of IT usage on performance and other organisation's outputs is an important issue for both practitioners and academics. Evidence shows that despite a vast percentage of firm's budget which has spent on IT is continuing increasingly, there are some failures of firms in obtaining the benefits of these expenditures within expected period. To solve this problem, managers have to consider complementary investments. In this paper a decision support system is developed for prioritising investments on the information technology (IT) and its complementary using data of 102 car part suppliers in Iran. This software is developed using an artificial neural network and results are validated finally. One of the main specifications of this DSS is investigating on IT aspects at the firm level, which can help top management during decision making process to allocate budget properly in the most significant aspects of IT investment inside their own company.